Preparation of nitrogen-doped carbon fiber packaged tin-cobalt alloy nanoparticle material and application of nitrogen-doped carbon fiber packaged tin-cobalt alloy nanoparticle material to negative electrode of lithium ion battery

By encapsulating tin cobalt alloy nanoparticle material by nitrogen-doped carbon fiber, the shortcomings of lithium-ion battery anode materials in ion reaction kinetics and conductivity are solved, and high-performance lithium-ion battery anode is achieved, reducing costs and improving cycle stability and magnification characteristics.

CN119297220AActive Publication Date: 2025-01-10INST OF NEW MATERIALS & IND TECH WENZHOU UNIV

Patent Information

Application Number
CN202411265620.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-10
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The lithium/sodium storage performance of existing lithium-ion battery anode materials is insufficient, especially tin-based materials have challenges in ion reaction kinetics and conductivity, and high processing costs and volume expansion lead to capacity attenuation and instability of the solid electrolyte phase film.

Method used

The tin cobalt alloy nanoparticle material is encapsulated with nitrogen-doped carbon fiber, and the complexation reaction is initiated by sodium citrate to form a CoSn(OH)6 precursor. After electrospinning and thermal reduction treatment, CoSn@C-N nanofibers are formed, and the carbon layer structure is used. Support and conducting networks improve the dispersion and charge transfer of lithium ions.

Benefits of technology

The cycle stability and magnification characteristics of the negative electrode of lithium-ion battery are significantly improved, the mechanical pressure caused by volume expansion is reduced, the service life of the battery is extended, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297220A_ABST
    Figure CN119297220A_ABST
Patent Text Reader

Abstract

The invention particularly relates to preparation of a nitrogen-doped carbon fiber packaged tin-cobalt alloy nanoparticle material and application of the nitrogen-doped carbon fiber packaged tin-cobalt alloy nanoparticle material to a negative electrode of a lithium ion battery. Through electrostatic spinning and thermal reduction methods, the CoSn-C-N composite material with N-doped carbon nanofibers embedded in CoSn alloy is prepared, and the CoSn-C-N composite material is applied to the negative electrode of the lithium ion battery. A large number of gaps exist among the CoSn alloy particles, stress caused by Sn volume change can be effectively reduced, and volume expansion is relieved; the highly dispersed CoSn nano-alloy particles are completely packaged in the porous carbon fibers, a considerable buffer space is also provided for volume expansion, and the carbon nanofibers not only can prevent structural fracture in the circulation process, but also are beneficial to electrolyte permeation, improve mass and load transfer capacity and enhance reaction kinetics. The preparation method disclosed by the invention is simple in process, low in cost and easier for large-scale production, and the prepared CoSn-coated C-N composite material is excellent in cycle performance and rate capability in a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery electrode materials, and specifically relates to the application of a nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle composite material in a lithium ion battery negative electrode. Background Art

[0002] Rechargeable lithium-ion batteries (LIBs) have attracted great attention as representative secondary energy storage devices. Due to their high energy density, long service life and environmental friendliness, the two types of batteries have been widely used in portable electronic products, electric vehicles and large-scale energy storage systems. Although commercial graphite has been widely used as anode in LIBs, the conventional graphite negative electrode material lithium / sodium storage process has limitations such as small capacity, poor cycle stability and high cost, so it is particularly important to find new high-efficiency and low-cost lithium / sodium storage negative electrode materials.

[0003] Studies have shown that tin (Sn) has an ultra-high theoretical specific capacity (4200mAh g -1 ) and a higher discharge platform than graphite and the ability to adapt to a wider voltage operating range have attracted widespread attention, thus becoming a new type of anode material. However, despite the above advantages, tin-based negative electrode materials face challenges such as slow ion reaction kinetics and poor conductivity in practice, high processing costs, and volume expansion during charging and discharging. A large number of attempts have been made to alleviate volume expansion, such as incorporating Sn into carbon matrices, making core-shell structures, and forming Sn-active metal (Sb, Bi, Ge) alloys / nanocomposites. However, when ions are deintercalated, the large volume change of Sn will cause severe fragmentation and instability of the solid electrolyte interphase (SEI), causing rapid fading of capacity, so it is very meaningful to design a reasonable carbon-based carrier. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material and a battery.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The first aspect of the present invention provides a nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material, and the preparation method thereof comprises the following steps:

[0007] S1. Dissolving a soluble cobalt salt and a soluble tin salt in a solvent to obtain a cobalt salt solution and a tin salt solution respectively, mixing the cobalt salt solution and the tin salt solution, and reacting the solution with sodium citrate to produce a complex reaction, and then etching the precursor with an alkaline solution to finally form CoSn(OH) with a hollow structure. 6 Particles;

[0008] S2, CoSn(OH) with hollow structure 6 The precursor is dispersed uniformly in N,N-dimethylformamide by ultrasonication, and then polyacrylonitrile and polymethyl methacrylate are added and stirred continuously to obtain a precursor solution;

[0009] S3, obtaining precursor nanofibers by electrospinning the precursor solution;

[0010] S4. The precursor nanofibers are thermally reduced to obtain CoSn@CN nanofibers.

[0011] Preferably, in step S1, the soluble cobalt salt is cobalt acetate tetrahydrate, and the soluble tin salt is tin tetrachloride pentahydrate.

[0012] Preferably, in step S1, the cobalt salt solution and sodium citrate are first mixed evenly, and then the tin salt solution is added to the mixed solution.

[0013] Preferably, in step S1, the alkaline solution is 1-3 mol·L -1 of sodium hydroxide solution.

[0014] Preferably, in step S2, CoSn(OH) 6 The mass volume ratio of N,N-dimethylformamide is 40-60:1.

[0015] Preferably, in step S2, the mass ratio of polyacrylonitrile to polymethyl methacrylate is 2-2.5:1.

[0016] Preferably, in step S3, the electrospinning distance is set to 13-17 cm, the voltage is 10-14 kV, and the spinning speed is 0.4-0.8 ml / h.

[0017] Preferably, in step S4, the thermal reduction specifically comprises the following steps:

[0018] S4.1, pre-oxidation: heat the temperature of the tube furnace to 210-250°C and maintain for 1-3 hours to complete pre-oxidation;

[0019] S4.2. Carbonization treatment: Raise the temperature of the tube furnace to 580-620°C for carbonization treatment and continue for 1-3 hours.

[0020] A second aspect of the present invention provides a lithium-ion battery, which uses the nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material as the negative electrode material.

[0021] Preferably, the preparation method comprises the following steps: uniformly mixing CoSn@CN nanofibers, acetylene black and sodium alginate in proportion, adding solvent and stirring into a paste, and coating the paste on copper foil; drying the copper foil, pressing the sheet, and assembling the battery to obtain the lithium ion battery.

[0022] The beneficial effects of the present invention are as follows: the present invention first uses (CH 3 COO 2 Co·4H 2 O and SnCl 4 ·5H 2 O as cobalt source and tin source, respectively, by adding C 6 H 5 Na 3 O 7 A large number of carboxyl groups are introduced into the solution, and these carboxyl groups react with Co 2+ and Sn 4+ The complexation reaction was carried out and finally the co-precipitation formed CoSn(OH) 6 The precursor is then etched by adding a certain concentration of NaOH, and then the hollow structure CoSn(OH) is obtained after centrifugal washing and drying. 6 Precursor: CoSn(OH) 6 Evenly dispersed in DMF and stirred to prepare a uniform electrospinning solution, CoSn(OH) 6 The hollow nanoblocks are confined in PMMA-PAN nanofibers with smooth surfaces; after high-temperature annealing, PMMA escapes with high-temperature decomposition and is replaced by CoSn(OH) 6 The derived uniformly dispersed CoSn alloy nanoparticles were embedded in N-doped carbon nanofibers. The material structure inside the nanofibers almost retained the precursor CoSn(OH) 6 The morphological state of the CoSn alloy is well understood, which provides strong support for achieving high-performance composite materials. With the structural support of the carbon layer and the connected electron transmission channels, the agglomeration and fragmentation of the CoSn alloy particles are significantly reduced, so the capacity decay is low. This shows that the covering effect of the carbon material effectively reduces the mechanical pressure caused by volume expansion, while the efficient conductive network, rich pore structure and size of the nanoparticles jointly promote the dispersion of lithium ions and the rapid transfer of charges.

[0023] The CoSn@CN nanofibers prepared in one embodiment of the present invention are used as LIB negative electrodes. It can be seen that the reversible capacity of the CoSn@CN material after 100 cycles is 612.2 mAh g -1 Similarly, at a current density of 1000 mA g -1 The reversible capacity of CoSn@CN material after 600 cycles is 525.2 mAh g -1 The discharge capacity of CoSn@CN is 0.1, 0.2, 0.5, 1, and 2 A g -1 Under the same conditions, they correspond to 772, 713, 604, 531, and 480 mAh g respectively. -1When the current density increases to 0.2A g -1 , its discharge capacity was restored to 710mAh g -1 , and maintained this capacity in subsequent cycles. The study fully demonstrated that the electrode material used exhibited excellent rate characteristics and high reversal capacity, highlighting the advantages of the hollow nano-block structure and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0025] Figure 1 (a, c) transmission electron micrographs of CoSn@CN nanofibers prepared in Example 1 and (b, d) transmission electron micrographs of tin-carbon nanofibers prepared in Comparative Example 1 without adding cobalt element;

[0026] Figure 2 (ac) SEM images, (df) TEM images, (j) HRTEM images, (h) SAED images and (i) EDS Mapping images of the CoSn@CN nanofiber material prepared in Example 1;

[0027] Figure 3 (a) is the X-ray diffraction pattern of CoSn@CN nanofibers prepared in Example 1; (b) is the X-ray diffraction pattern of tin-carbon nanofibers prepared in Comparative Example 1 without adding cobalt element;

[0028] Figure 4 The CoSn@CN nanofiber negative electrode material prepared in Example 1 and the tin carbon nanofiber prepared in Comparative Example 1 without adding cobalt element were used as negative electrodes for lithium ion batteries at a low current of 100 mA g -1 (a) and 1000mA g -1 (b) and cycle stability test diagram at different current densities (c). DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0030] Embodiment 1:

[0031] A method for preparing a high-performance lithium storage negative electrode material of tin-cobalt alloy nanoparticles encapsulated with nitrogen-doped carbon fiber, the steps are as follows:

[0032] S1: Weigh 3 mmol of cobalt acetate and 3 mmol of sodium citrate and dissolve them uniformly in 45 ml of deionized water, respectively, called solution A and solution B, add solution B dropwise into solution A, stir with a magnetic stirrer to form a uniform mixed solution, then weigh 3 mmol of tin tetrachloride pentahydrate and dissolve them uniformly in 15 ml of ethanol solution, called solution C, add solution C dropwise into the mixed solution of A and B to form a uniform solution D, then add 2 mol L -1 15 ml of sodium hydroxide solution was stirred in a water bath at 25 °C for 2 h, and then 8 mol L -1 60 mL of sodium hydroxide solution was added and reacted for 15 min to obtain the precursor cobalt tin hydroxide CoSn(OH) 6 ;

[0033] S2: Take 500mg CoSn(OH) 6 Dissolve in 10 ml of N,N-dimethylformamide (DMF) and disperse with ultrasound for 1 h;

[0034] S3: 0.9 g of polyacrylonitrile (PAN) and 0.4 g of polymethyl methacrylate (PMMA) were added to the solution in sequence, and magnetic stirring was used for 24 h to prepare a uniform precursor solution;

[0035] S4: The solution was loaded into a 10 mL plastic syringe for electrospinning. During spinning, the distance was set to 15 cm, the voltage was 12 kV, and the spinning speed was 0.6 ml / h;

[0036] S5: Pre-oxidation and then carbonization of the precursor nanofibers were performed using a tube furnace. During the process, the precursor nanofibers were first heated to 230°C at a rate of 2°C / min and maintained for 2 hours to complete the pre-oxidation.

[0037] S6: Subsequently, the temperature is raised to 600°C at a rate of 2°C / min for carbonization treatment, and the treatment is continued for 2 hours to obtain the final product CoSn@CN nanofiber material.

[0038] S7: Weigh CoSn@CN nanofiber material, acetylene black and sodium alginate in a mass ratio of 7:2:1, mix evenly, add appropriate amount of ultrapure water, stir continuously into a paste, and apply it on copper foil; dry the copper foil, press it into sheets, and assemble the battery to obtain a lithium ion battery.

[0039] Comparative Example 1:

[0040] The preparation process of this comparative example is substantially the same as that of Example 1, with the only difference being that in step S1, no cobalt element is introduced, and tin nanofibers (Sn@CN) are synthesized by comparison.

[0041] Tin nanofiber (Sn@CN) material, acetylene black and sodium alginate are weighed and mixed evenly in a mass ratio of 7:2:1, an appropriate amount of ultrapure water is added, and the mixture is continuously stirred into a paste, which is then coated on a copper foil; the copper foil is dried, pressed into sheets, and a battery is assembled to obtain a lithium-ion battery.

[0042] Microscopic characterization

[0043] The following are the microscopic characterizations of different methods for the synthesis of large-scale tin oxide nanosheets composite graphene high-performance lithium storage materials by surfactant adsorption:

[0044] Figure 1 The scanning electron microscope (TEM) images (a) and (c) of the CoSn@CN nanofibers prepared in Example 1 and the scanning electron microscope (b) and (d) of the Sn@CN prepared in Comparative Example 1 without adding cobalt. The transmission electron microscope (TEM) images of the CoSn@CN and Sn@CN composite materials clearly show that both materials are wrapped by carbon nanofibers. Figure 1 From (a) and (c), we can see that the surface of the carbon fiber is relatively smooth, and the alloy particles are evenly wrapped inside the carbon fiber. It can be clearly observed that the CoSn alloy particles are completely wrapped by carbon fibers with a diameter of about 150nm, and the size is uniform, which shows that the sample spinning technology has been successfully applied. Figure 1 (b) (d) Sn@CN is a morphology of large particle nanospheres being entangled by spinning. It can be seen from the figure that the size of the formed Sn particles is about 1μm, which is tightly wrapped by some carbon nanofibers, but not completely wrapped. 2 The huge particles cannot enter the interior of the spun fibers and cannot take advantage of the structural advantages of carbon fiber.

[0045] Figure 2(ac) SEM images, (df) TEM images, (j) HRTEM images, (h) SAED images and (i) EDS Mapping images of the CoSn@CN nanofiber material prepared in Example 1. It can be seen from the figure that the CoSn bimetallic particles are irregularly round in shape, with a diameter of about 60nm, and are completely embedded in the amorphous carbon layer. The measurement shows that the spacing between the crystal stripes is 0.22nm, which points to the (111) crystal plane of the hexagonal CoSn particles. In addition, two other crystal planes, namely (102) and (220), were confirmed by means of selected area electron diffraction (SEAD) rings. This matches the diffraction peaks detected in X-rays. Figure (i) shows the element distribution of the CoSn@CN material. Studies have shown that the CoSn alloy particles are evenly dispersed at the edge and center of the sample, while the C and N elements are mainly distributed in the outer layer of the sample. This phenomenon verifies that the particles of the CoSn bimetallic compound have been completely encapsulated by the amorphous nitrogen impurity-doped carbon material, forming a characteristic hollow nanostructure.

[0046] Figure 3 (a) is the X-ray diffraction (XRD) pattern of CoSn@CN nanofibers prepared in Example 1; (b) is the X-ray diffraction (XRD) pattern of tin-carbon nanofibers prepared in Comparative Example 1 without adding cobalt element.

[0047] Electrochemical performance characterization

[0048] Figure 4 The CoSn@CN nanofiber negative electrode material prepared in Example 1 and the tin carbon nanofiber prepared in Comparative Example 1 without adding cobalt element were used as negative electrodes for lithium ion batteries at a low current of 100 mA g -1 (a) and 1000mA g -1 (b) and cycle stability test diagram at different current densities (c). CoSn@CN and Sn@CN materials at a current density of 100mAg -1 It can be seen that the reversible capacity of CoSn@CN material after 100 cycles is 612.2 mAh g -1 , which is better than Sn@CN material (473.1mAh g -1 ), similarly, at a current density of 1000 mA g -1 It can be seen that the reversible capacity of CoSn@CN material after 600 cycles is 525.2 mAh g -1 , which is better than Sn@CN material (337.1mAh g -1 ).

[0049] In summary, in the present invention, a CoSn@CN carbon-based composite material embedded with N-doped carbon nanofibers is prepared by a simple electrospinning technology and a thermal reduction strategy, and is applied to the negative electrode of lithium-ion batteries and sodium-ion batteries. The structural design of CoSn@CN nanofibers provides certain advantages for lithium storage / sodium storage reactions. First, the introduction of an inactive metal Co matrix and its voids into the hollow block CoSn alloy can effectively reduce the stress caused by the volume change of Sn and effectively alleviate the volume expansion. In addition, the complete encapsulation of highly dispersed CoSn nano alloy particles in porous carbon fibers also provides a considerable buffer space for volume expansion. The carbon nanofibers can not only prevent structural fractures during the cycle, but also facilitate the penetration of electrolytes, improve mass transfer and load transfer capabilities, and enhance reaction kinetics. Compared with existing reports, the preparation method of the present invention is simple in process, low in cost, and easier to mass produce. The obtained CoSn@CN composite material has excellent cycle performance and rate performance in lithium-ion batteries and sodium-ion batteries.

[0050] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material, characterized in that: The preparation method thereof comprises the following steps: S1. Dissolving a soluble cobalt salt and a soluble tin salt in a solvent respectively to obtain a cobalt salt solution and a tin salt solution, mixing the cobalt salt solution and the tin salt solution, and reacting the solution with sodium citrate to produce a complex reaction, and then etching the precursor with an alkaline solution to finally form CoSn(OH)6 particles with a hollow structure; S2, uniformly dispersing the CoSn(OH)6 precursor having a hollow structure in N,N-dimethylformamide by ultrasonication, and then adding polyacrylonitrile and polymethyl methacrylate and continuing to stir to obtain a precursor solution; S3, obtaining precursor nanofibers by electrospinning the precursor solution; S4. The precursor nanofibers are thermally reduced to obtain CoSn@CN nanofibers.

2. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S1, the soluble cobalt salt is cobalt acetate tetrahydrate, and the soluble tin salt is tin tetrachloride pentahydrate.

3. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S1, the cobalt salt solution and sodium citrate are firstly mixed evenly, and then the tin salt solution is added to the mixed solution.

4. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S1, the alkaline solution is 1-3 mol·L -1 of sodium hydroxide solution.

5. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S2, the mass volume ratio of CoSn(OH)6 to N,N-dimethylformamide is 40-60:

1.

6. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S2, the mass ratio of polyacrylonitrile to polymethyl methacrylate is 2-2.5:

1.

7. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S3, the electrospinning distance is set to 13-17 cm, the voltage is 10-14 kV, and the spinning speed is 0.4-0.8 ml / h.

8. The nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material according to claim 1, characterized in that: In step S4, the thermal reduction specifically includes the following steps: S4.1, pre-oxidation: heat the temperature of the tube furnace to 210-250°C and maintain for 1-3 hours to complete pre-oxidation; S4.

2. Carbonization treatment: Raise the temperature of the tube furnace to 580-620°C for carbonization treatment and continue for 1-3 hours.

9. A lithium ion battery, characterized in that: The method adopts the nitrogen-doped carbon fiber encapsulated tin-cobalt alloy nanoparticle material as claimed in any one of claims 1 to 8 as the negative electrode material.

10. The lithium ion battery according to claim 9, characterized in that: The preparation method comprises the following steps: uniformly mixing CoSn@CN nanofibers, acetylene black and sodium alginate in proportion, adding solvent and stirring into a paste, and coating the paste on copper foil; drying the copper foil, pressing the sheet and assembling the battery to obtain the lithium ion battery.

Citation Information

Patent Citations

  • Preparation for anode material of tin-cobalt alloy / carbon nanofiber film lithium ion battery

    CN102751475A

  • Tin phosphide-based composite material as well as preparation method and application thereof

    CN117936718A

  • Method of operating a lithium-ion cell having a high-capacity cathode

    US20130271085A1

  • Nitrogen-doped and carbon matrix-encapsulated silicon-carbon nanofiber composite, method for preparing same, and secondary battery comprising same

    WO2023239046A1

Cited By

  • Negative electrode material based on SnS / CoS bi-component metal sulfide as well as preparation method and application of negative electrode material

    CN122576086A